Application of Integrated Flood Analysis System (IFAS) for Dungun river basin - Hafiz I.; Nor N.D.M.; Sidek L.M.; Basri H.; Hanapi M.N.; Livia L. (Institute of Physics Publishing, 2023)
The Northeast monsoon happening during the months of October until January is the major rainy season found in the eastern part of Peninsular Malaysia. The Dungun river basin (1,858 km2) is exposed to this season thus experiencing characteristically regular flooding due to the prolong rainfall events. The annual rainfall over the river basins are 2,880 mm with great proportion falling in the months of December (19.4%). This study is to apply the Integrated Flood Analysis System (IFAS) model which Dungun river basin has been chosen for this study as the catchments have range of flood and relevant data that can be used to develop the model. The satellite data used in this study is provided by JAXA Global Rainfall Watch. The main feature of this real-time flood analysis model is the satellite-based rainfall data input employed during the model creation phase. The performance of the model for the river basins from satellite and ground-based rainfall data are compared using three error analysis methods. Published under licence by IOP Publishing Ltd.